Islamic economics as an integrated social science: novel ideas on its foundations - Mohd Yusop, Mohd Mahyudi (2018)
One positive response to the Great Recession (2008-2012) is that economics is seriously rethinking on its future shape and direction. As value-free economics begins to wane, Putnam’s (2012) ‘second phase classical theory’ and ‘entanglement of fact and value’ notions look encouraging. Therein lies openings for Islamic economics to project itself as an integrated social science. To that end, our approach is two-fold. Firstly, we critically look into Nienhaus’ (2013) four problems of Islamic economics. Incisively, we assert that Islamic economics is still a widely disregarded field; its normative element is not a hindrance to constructive engagement; growth in ‘Islamic economics light’ research is a boon; and Islamic economic practice has an inherent political economy character. The coherency of our integrated science idea is well-displayed in our arguments. Secondly, we proffer novel insights on epistemological and micro-foundational matters to be applied in future Islamization endeavours. On Islamic epistemology, reason and rationality must be conditioned by the concepts of existence, intelligibility, and moral thinking. We find Kalin’s (2015) position consistent with the expected cognitive conduct for Islamic economists. About the micro-foundation issue, the inadequacy of both homo economicus and homo Islamicus concepts is highlighted. So, the ‘universal man’ proposal is given due weight. We utilise Mahyudi and Aziz’s (2017) new definition of Islamic economics and ‘Quranic framework’ in elaborating on substance and methodology of the discipline throughout this paper. Finally, with enhanced intellectual clarity, we are optimistic about the prospect of Islamic economics furthering the Islamization of knowledge agenda.